Prognostic Value of Deep Learning-Mediated Treatment Monitoring in Lung Cancer Patients Receiving Immunotherapy - Trebeschi, Stefano; Bodalal, Zuhir; Boellaard, Thierry N.; Tareco Bucho, Teresa M.; Drago, Silvia G.; Kurilova, Ieva; Calin-Vainak, Adriana M.; Delli Pizzi, Andrea; Muller, Mirte; Hummelink, Karlijn; Hartemink, Koen J.; Nguyen-Kim, Thi Dan Linh; et al. (Frontiers in Oncology, 2021)
Background. Checkpoint inhibitors provided sustained clinical benefit to metastatic lung cancer patients. Nonetheless, prognostic markers in metastatic settings are still under research. Imaging offers distinctive advantages, providing whole-body information non-invasively, while routinely available in most clinics. We hypothesized that more prognostic information can be extracted by employing artificial intelligence (AI) for treatment monitoring, superior to 2D tumor growth criteria. Methods. A cohort of 152 stage-IV non-small-cell lung cancer patients (NSCLC)(73 discovery, 79 test, 903CTs), who received nivolumab were retrospectively collected. We trained a neural network to identify morphological changes on chest CT acquired during patients' follow-ups. A classifier was employed to link imaging features learnt by the network with overall survival. Results. Our results showed significant performance in the independent test set to predict 1-year overall survival from the date of image acquisition, with an average area under the curve (AUC) of 0.69 (p<0.01), up to AUC 0.75 (p<0.01) in the first 3-5 months of treatment, and 0.67 AUC (p=0.01) for durable clinical benefit (6-months progression-free survival). We found the AI-derived survival score to be independent of clinical, radiological, PDL1, and histopathological factors. Visual analysis of AI-generated prognostic heatmaps revealed relative prognostic importance of morphological nodal changes in the mediastinum, supraclavicular and hilar regions, lung and bone metastases, as well as pleural effusions, atelectasis and consolidations. Conclusions. Our results demonstrate that deep learning can quantify tumor- and non-tumor related morphological changes important for prognostication on serial imaging. Further investigation should focus on the implementation of this technique beyond thoracic imaging.